Reported History of Measles and Long-term Impact on Antibody to Tetanus in Children 6–59 Months of Age Receiving DTP in the Democratic Republic of Congo. (4th October 2017) - Ashbaugh, Hayley; Cherry, James D; Gerber, Sue; Higgins, Stephen G; Gadoth, Adva; Alfonso, Vivian H; Mukadi, Patrick; Hoff, Nicole; Doshi, Reena; Rimoin, Anne W
Abstract: Background: Recent studies suggest a measles-induced immune amnesia that could have long-term immunosuppressive effects via preferential depletion of memory B and T CD150+ lymphocytes. Methods: We examined the association between past measles and tetanus antibody levels among children participating in the 2013–2014 Democratic Republic of Congo (DRC) Demographic and Health Survey (DHS). Our sample consisted of 833 children aged 6–59 months whose mothers were selected for interview. Mothers reported (via recall) history of measles within the lifetime of the child. Classification of children who previously had measles was completed using maternal recall and measles immunoglobulin G (IgG) serostatus obtained via dried blood spot (DBS) analysis. A multiplex chemiluminescent immunoassay platform was used to obtain serologic results and Assay Score (AS) was calculated as a ratio to a positive control included in each run. Tetanus serostatus was categorized as being above or below the sample median serology AS value. Tetanus vaccination status was obtained via dated vaccination card and limited to children receiving the complete 3-dose vaccination series. Results: The median AS for tetanus serology among the entire sample of 833 children was 0.085, while children with history of measles had a median AS of 0.053 ( N = 41) and children with no history of measles had a median AS of 0.088 ( N = 792), chi-square P -value < 0.05. A random intercept logistic regression model was used to examine the association between previous measles disease and odds of having below median levels of tetanus antibody. Controlling for potential confounding variables, the odds of a child with past history of measles having less than the median level of tetanus antibody was 3.86 (95% CI: 1.70, 8.78) among children fully vaccinated for tetanus. Conclusion: The results suggest that, among children 6–59 months in DRC, measles may have a long-term impact on levels of pre-existing, vaccine-induced immunity to tetanus. These findings suggest the need for laboratory studies examining measles' impact on pre-existing, vaccine-induced immunity and underscore the need for continued evaluation and improvement of DRC's measles vaccination program. Disclosures: All authors: No reported disclosures.